2022
DOI: 10.3390/act11020056
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Model-Based Verification of an Emergency Strategy for Cable Failure in Cable Robots

Abstract: Cable failure is an extremely critical situation in the operation of cable-driven parallel robots (CDPR), as the robot might be instantly outside of its predefined workspace. Therefore, the calculation of a cable force distribution might fail and, thus, the controller might not be able to master the guidance of the system anymore. However, as long as there is a remaining set of cables, the dynamic behavior of the system can be influenced to prevent further damage, such as collisions with the ground. The paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Furthermore, recovery strategies for a safe cable release outside the RSFW will be investigated. Beyond simply stopping the robot, other approaches such as a partial cable release or solutions designed for post-870 cable failure recovery could be used [34,35,36]. The implementation and improvement of such methods, ensuring safety of the operators in the whole workspace without stopping the robot and reinitialize it manually, are important steps towards the use of collaborative CDPRs in the industry.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recovery strategies for a safe cable release outside the RSFW will be investigated. Beyond simply stopping the robot, other approaches such as a partial cable release or solutions designed for post-870 cable failure recovery could be used [34,35,36]. The implementation and improvement of such methods, ensuring safety of the operators in the whole workspace without stopping the robot and reinitialize it manually, are important steps towards the use of collaborative CDPRs in the industry.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Passarini et al. (2019) studied emergency stop strategies for preventing collisions in cable suspended robots, whereas Boumann and Bruckmann (2022) focused on a force control strategy in the remaining cables of a cable-suspended robot to minimize the safety risk of dynamic effects during cable failures in the workspace. The authors assumed that the cable failures, when triggered, were always correctly identified and the proposed control framework was restricted to a post-failure setting.…”
Section: Related Workmentioning
confidence: 99%
“…Le Nguyen and Caverly (2021); Korayem et al (2018); Caverly and Forbes (2016) addressed the futility of relying on forward kinematics from cable length measurements to determine end-effector pose, reasoning that encoder measurements do not necessarily correspond to the true cable length, which may be affected by unknown deformations Other literature on CDPR cable failures focused on dynamic failure recovery strategies or dynamic collision avoidance strategies. For instance, Passarini et al (2019) studied emergency stop strategies for preventing collisions in cable suspended robots, whereas Boumann and Bruckmann (2022) focused on a force control strategy in the remaining cables of a cable-suspended robot to minimize the safety risk of dynamic effects during cable failures in the workspace. The authors assumed that the cable failures, when triggered, were always correctly identified and the proposed control framework was restricted to a post-failure setting.…”
Section: Related Workmentioning
confidence: 99%